Aspirin Intolerance in the Setting of Acute Coronary Syndrome: Case Report and Review of Literature - Temirbek Janpaizov; Ilvira Ibraimova; Erlan Zhumagulov; Kaisar Dauyey (Ķazaķstannyṇ Klinikalyķ Medicinasy)
Acute coronary syndrome (ACS) requires prompt intervention to prevent myocardial ischemia. This case report describes a patient’s clinical journey, highlighting the challenges associated with aspirin intolerance and the necessity of an alternative antithrombotic approach. The patient, who presented with ACS and a documented history of aspirin-induced asthma and angioedema, was unable to undergo standard dual antiplatelet therapy (DAPT) with aspirin. Given the urgency of intervention and failed prior aspirin desensitization, ticagrelor and rivaroxaban were selected as alternative agents. The patient underwent successful percutaneous coronary intervention (PCI) with stent placement and was managed postoperatively using a modified antithrombotic regimen. The case underscores the importance of individualized therapy in aspirin-intolerant ACS patients and suggests a viable alternative strategy for anticoagulation and platelet inhibition. Patient outcomes were favorable, demonstrating effective ischemic risk mitigation without aspirin-related hypersensitivity reactions.